The Mediating Role of Organizational Commitment in the Relationship between Participative Leadership and Job Performance of Insurance Agents in Surabaya - Marshella Sheren Monica; Fenika Wulani; P. Julius F. Nagel (Telaah Bisnis, 2023)
This study analyzes the effect of participative leadership and organizational commitment on the job performance of insurance agents in Surabaya. The research also identifies the mediating role of organizational commitment in the relationship between participative leadership and job performance. Data collection by distributing questionnaires resulted in 94 responses. The data is analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that all the hypotheses are supported. Participative leadership and organizational commitment have a positive effect on job performance. In addition, organizational commitment mediates the relationship between participative leadership and job performance.  This study supports social exchange theory. Moreover, this study's findings show the importance of insurance companies selecting and developing individuals in managerial positions who are able to behave participatively.